Finite elements with embedded multiple cracks and non-uniform discontinuity modes - Manzoli, O. L.; Shing, P. B. (My University, 2005)
Recently, several formulations of finite elements embedded with displacement discontinuity have been proposed to describe crack propagation independent of the element boundaries. By construction, these approaches are limited to represent a single crack in the element with uniform discontinuity modes (opening and sliding). This paper presents a procedure to embed displacement discontinuities in quadrilateral finite elements that is suitable for incorporating multiple discontinuities or non-uniform discontinuity modes. These capabilities may be essential to predict failure in reinforced concrete. Basic tests are performed to access the effectiveness of the proposed technique.